Comparative Genome Analysis of 2 Mycobacterium Tuberculosis Strains from Pakistan: Insights Globally Into Drug Resistance, Virulence, and Niche Adaptation. (20th July 2018) - Yar, Asma Muhammad; Zaman, Ghanva; Hussain, Annam; Changhui, Yan; Rasul, Azhar; Hussain, Abrar; Bo, Zhu; Bokhari, Habib; Ibrahim, Muhammad
Multidrug-resistant Mycobacterium tuberculosis is a global threat particularly in developing countries like Pakistan. In this study, we identified 2 M tuberculosis strains, mnpk and swlpk, by 16S RNA genes, sequenced their draft genome, and compared the 2 genomes with reference strain H37Rv and gene expression analysis of selected virulent genes. Phylogenetic analysis of M tuberculosis strains, mnpk and swlpk, using 16S RNA genes revealed that the strains are closely related with reference strain H37Rv. The draft genome sequence of mnpk and swlpk contains 4305 and 4295 protein-coding genes, respectively, having 99.9% with high collinearity when compared with H37Rv. Although some important drug-resistant genes such as fabG, faDE24, and iniA were missing, genome mining also revealed key drug-resistant genes such as katG, inhA, rpoA, rpoB, and rpoC against first-line isoniazid and rifampicin drug. The strain mnpk and swlpk encodes 257 putative and 86 verified virulent genes including type 7 secretion system (T7SS) key genes. The variation in the expression profile of selected T7SS genes, particularly low expression level of EspK, raised concern that the mechanism of virulence of mnpk and swlpk might be different from H37Rv strains as espK is associated with ATPase EccC1a and EccC1b which showed high expression level. Briefly, this study shows that the strains mnpk and swlpk are linked with H37Rv having 99% similarity in genomes, but the absence of drug-resistant genes and variation in key genes' expression profile espK, EccE1, PPE41, and espC provide a rationale for the future investigation of M tuberculosis mnpk and swlpk pathogenesis via RNA sequencing, single-nucleotide polymorphisms, as well as gene manipulation.